Enhancing rapeseed (Brassica napus L.) productivity through frontline demonstrations approach in Ferozepur district of Punjab (Journal of Oilseed Brassica, 2026)
Frontline demonstrations were conducted in district Ferozepur on canola variety of gobhi sarson during the year 2018- 19 with the objective to enhance production and productivity of canola gobhi srason with economic benefits at farmer’s field through improved production technologies. The results of the study revealed that GSC-7 canola gobhi sarson variety gave average yield of 22.5 q/ha as compared to 17.8 q/ha of local variety with an increase in yield of 26.4% over local variety. Moreover, the cultivation of canola gobhi sarson (GSC-7) under frontline demonstrations yielded additional gain of Rs. 19480/ha over farmer’s practice.